The Effect of Intravenous Induction of Anesthesia on the Hemodynamic Changes among Patient in Central Surgical Unit of Level-II Udayana Denpasar Hospital - Emanuel Ileatan Lewar; I Wayan Agus Maharyawan; Yustina Ni Putu Yusniawati; Carles Takandjandji (Babali Publisher, 2022)
Introduction: Intravenous anesthetic induction is a medically-induced technique that can cause hemodynamic disorder. The impact that occurs if hemodynamic disorders are not immediately resolved in patients with intravenous anaesthesia induction can cause an increase or decrease in blood pressure, decreased tissue perfusion, increased heart rate and arrhythmias so that it disrupts the surgical action plan. Blood pressure, Mean Arterial Pressure (MAP), and pulse should be monitored carefully during induction. We ought to examine the effect of intravenous induction of anesthesia on the hemodynamic changes among patients in the Level-II Udayana Denpasar Hospital. Methods: This was a descriptive cross-sectional study with a consecutive sampling technique. All patients under intravenous induction of anesthesia were considered eligible study respondents. Data were collected using an observation sheet, The number of samples in this study were 60 respondents, and the statistical test used a univariate technique by looking at the frequency distribution of the hemodynamic features of the patient's blood pressure and pulse. Results: Findings reported that the majority of patients were documented with normal systolic blood pressure (51: 85.0%), normal MAP (56; 93.3%), and normal pulse rate (44; 73.3%) during the intravenous induction. Low diastolic blood pressure was reported among 33 respondents (55.5%). Conclusion: The intravenous anesthetic induction altered the hemodynamic status among the respondents.